Researches on the geochemistry of the uranium: autoradiographic study on the α• radioactivity distribution in the most important facies of the biella pluton. (western alps) (1962)
The α-radioactivity distribution in the principal facies of the Biella pluton has been recognized. The data has been comparated with those of other investigators. The constancy of some relations between the activity of the minerals and their inclusions has been put on evidence.